2009
DOI: 10.1098/rspb.2008.1318
|View full text |Cite
|
Sign up to set email alerts
|

Life on the edge: carnivore body size variation is all over the place

Abstract: Evolutionary biologists have long been fascinated by both the ways in which species respond to ecological conditions at the edges of their geographic ranges and the way that species' body sizes evolve across their ranges. Surprisingly, though, the relationship between these two phenomena is rarely studied. Here, we examine whether carnivore body size changes from the interior of their geographic range towards the range edges. We find that within species, body size often varies strongly with distance from the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 60 publications
2
30
2
Order By: Relevance
“…Alternatively, individuals tend to be larger towards higher latitudes. Populations distributed along a North-South axis therefore tend to show larger individuals near one of the edges rather than the core [66], [67]. Our results, confirmed this last tendency of larger size at higher latitudes, with A. quadrispinosa showing a ramped south distribution of size.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Alternatively, individuals tend to be larger towards higher latitudes. Populations distributed along a North-South axis therefore tend to show larger individuals near one of the edges rather than the core [66], [67]. Our results, confirmed this last tendency of larger size at higher latitudes, with A. quadrispinosa showing a ramped south distribution of size.…”
Section: Discussionsupporting
confidence: 83%
“…[15]). Some studies suggest that larger individuals occur at the core of the range (in agreement with the ACH) where the habitat is most suitable [11], [12], [66]. Alternatively, individuals tend to be larger towards higher latitudes.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, previous studies have shown a positive fit between body size variation and latitude in badgers (Meiri & Dayan, 2003; Meiri et al. , 2004), although Meiri et al. (2009) found some support for the ACH.…”
Section: Introductionmentioning
confidence: 75%
“…, 2005). Only recently, Meiri et al. (2009) showed that the relationship between body size variation and position within the range (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the extent to which these are general patterns, or the circumstances under which they do and do not emerge, remain poorly understood. In this special issue, in exploring the case of spatial variations in body size using the carnivores as a study system, Meiri et al (2009) document the complexity that can arise and the importance of examining large numbers of species. Likewise, drawing on a vast dataset for species of trees in the eastern USA, Purves (2009) examines the, from an empirical perspective surprisingly neglected, pattern of change in demographic rates between the core and limit of geographic ranges.…”
Section: Abstract: Ecology; Evolution; Geographic Rangementioning
confidence: 99%